Modelling fluid and particulate flow through a ventriculoperitoneal shunt in a variable temperature environment - Ramokoka Tshiamo (EDP Sciences, 2021)
One of the most prevalent causes of failure for a ventriculoperitoneal shunt is blockage, the other being infection. This study looks at the blockage of the shunt valve, and whether the occlusion of a shunt valve is accelerated by the presence of an infection. This study assumes that an infection will raise the number of white blood cells contained in the cerebrospinal fluid to fight it and will thus accelerate shunt occlusion. The experiment simulates a shunt system by suspending a shunt valve in a water bath that has a temperature that varies between 37°C and 41°C. A computational fluid dynamics model of the shunt system is used to gain further insight into the flow behaviour under these conditions. The results of the CFD model were validated using the experimental results. There was an average error of 15% between the readings that were obtained in the experiment and the CFD model. The experimental results showed that there was a decrease in the volume flow rate at the outlet of the shunt system, which was not large enough to point towards any blockage. Both the model predictions and the experimental results show that increased temperature and particulate concentration alone do not result in shunt occlusion, particularly at the shunt valve. This result effectively excluded the shunt valve as a region of shunt occlusion due to infection, as an infection occurs due to the growth of bacteria along the surfaces of the shunt system and this bacterial growth is more likely to occur at the proximal and distal ends of the shunt system.